Individual and Neighborhood Factors Associated With Failure to Vaccinate Against Influenza During Pregnancy. Issue 11 (31st July 2020) - Zerbo, Ousseny; Ray, G Thomas; Zhang, Lea; Goddard, Kristin; Fireman, Bruce; Adams, Alyce; Omer, Saad; Kulldorff, Martin; Klein, Nicola P
Abstract: Uptake of influenza vaccine among pregnant women remains low. We investigated whether unvaccinated pregnant women were clustered geographically and determined factors associated with failure to vaccinate using spatial and multivariate logistic regression analyses. Pregnant women who were members of Kaiser Permanente Northern California in 2015 or 2016 were included in the study. More than half (53%) of the 77, 607 included pregnant women were unvaccinated. Spatial analysis identified 5 clusters with a high prevalence of unvaccinated pregnant women. The proportion of unvaccinated women ranged from 57% to 75% within clusters as compared with 51% outside clusters. In covariate-adjusted analyses, residence in a cluster was associated with a 41% increase in the odds of being unvaccinated (odds ratio (OR) = 1.41, 95% confidence interval (CI): 1.36, 1.46). The odds of being unvaccinated were greater for Black women (OR = 1.58, 95% CI: 1.49, 1.69), Hispanic women (OR = 1.15, 95% CI: 1.05, 1.25), women with subsidized health insurance (OR = 1.18, 95% CI: 1.11, 1.24), women with fewer than 5 prenatal-care visits (OR = 1.85, 95% CI: 1.60, 2.16), and neighborhoods with a high deprivation index (fourth quartile vs. first: OR = 1.14, 95% CI: 1.07, 1.21). In conclusion, unvaccinated pregnant women were clustered geographically and by key sociodemographic factors. These findings suggest that interventions to increase influenza vaccine coverage among pregnant women are needed, particularly in vulnerable populations.